ANALISIS KADAR ALP (ALKALINE PHOSPATASE) PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS GAMBESI KOTA TERNATE SELATAN - Jakaria, Febrianti; Nikma; Irma Berliana Hi. Lewa; Samad Hi. Husen (Jurnal Analis Kesehatan Kendari, 2024)
ALP is present in almost all body tissues, starting from the liver, kidneys, intestines and placenta. The placenta in pregnant women is a food transport medium from mother to fetus with the help of the ALP enzyme, where the ALP enzyme breaks down proteins into amino acids. ALP is an enzyme used to assess hepatocellular and hepatobiliary disorders. This enzyme is found in bones, liver and placenta. ALP in liver cells is found in sinusoids and bile duct membranes, apart from that, ALP is often found in osteoblast activity. Normal values ​​are higher in children, pregnant women and in bone injuries. Objective: Determine ALP levels in third trimester pregnant women in the working area of ​​the Gambesi Community Health Center. Method: The type of research used in this research is descriptive. Descriptive research is carried out on a group of objects which usually aims to describe or provide an overview of the object being studied as it is without carrying out analysis. Results: In this study, the sample used was 23 people obtained from pregnant women in the third trimester in the working area of ​​the Gambesi Health Center, South Ternate City using accidental sampling. Based on the research results, examination of ALP levels obtained high results from 21 respondents and normal results from 2 respondents. Conclusion: Based on the results of research on ALP (Alkaline phosphatase) levels in pregnant women in the third trimester in the working area of ​​the Gambesi Health Center, South Ternate City using the Selectra Pro Xs and Microlab 300 tools. An increase in ALP levels was found in 21 respondents and 2 respondents were normal.